EVOLUTION OF PRODUCTION AND TECHNOLOGICAL STRUCTURE OF OIL-PROCESSING INDUSTRY OF RUSSIA - A. Solomonov (Вестник университета)
In the article the retrospective analysis of formation of production structure of oil-processing industry of Russia is carried out. The special attention is paid to formation of corporate structure of the industry. Factors of further development of the industry are analysed.